Gastric leiomyoblastoma. Issue 10 (October 1970) - Bose, B.; Candy, J.
Abstract : This paper describes two cases of gastric leiomyoblastoma (bizarre smooth muscle tumour), one of them having evidence of metastases. Both patients remain well after seven years and three and a half years respectively. The literature is reviewed, and the clinical features, diagnosis, and treatment are discussed. The histological appearances are described in detail and an attempt is made to assess the criteria for the diagnosis of malignancy.